PERAN PEMERINTAH KABUPATEN BENGKALIS DALAM MENYELESAIKAN KONFLIK PERTANAHAN ANTARA PT.ARARA ABADI DENGAN MASYARAKAT HUKUM ADAT SUKU SAKAI DUSUN SULUK BONGKAL, DESA KOTO PAIT BERINGIN, KECAMATAN TALANG MUANDAU, KABUPATEN BENGKALIS TAHUN 2019-2020 - Evi Perawati; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Bengkalis Regency actually has many unity of indigenous law communities and ulayat land in every village, especially in Riau Province. In Bengkalis Regency itself the existence of indigenous law communities is better known as Sakai which is under the Batin. Speaking of the existence of indigenous law communities and their traditional rights have been guaranteed in the 1945 Constitution. This research aims to find out how the Role of the Bengkalis Regency Government in Resolving Land Conflicts Between PT. Arara Abadi with the Indigenous Law Community of Sakai Dusun Suluk Bongkal Village Koto Pait Beringin Talang Muandau District Bengkalis,  then also to find out what are the obstacles and obstacles experienced by the Bengkalis Regency Government in resolving conflicts between PT. Arara Abadi with the Sakai Indigenous Law community. The research location was conducted in Suluk Bongkal Village Koto Pait Beringin District Talang Muandau Bengkalis Regency. Furthermore, data collection techniques are carried out with interviews, documentation, and library studies.  The result of this study is the Role of the Bengkalis Regency Government in Resolving Land Conflicts Between PT. Arara Abadi With The Indigenous Law Community of Sakai Tribe Suluk Bongkal Village Koto Pait Beringin Talang Muandau District Bengkalis Regency which was done as an effort to find out the role of the district government in resolving the conflict between the indigenous law communities of sakai tribe and PT. Arara Abadi. Resolution of conflicts between the indigenous peoples of the Sakai tribe and PT. Arara Abadi has not been running optimally. This is due to several obstacles such as the release of the rights of indigenous peoples by the District Government.Keywords: Role, Conflict, Indigenous Law Society.